2018
DOI: 10.3390/molecules23040729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Limited Hydrolysis and High-Pressure Homogenization on Functional Properties of Oyster Protein Isolates

Abstract: In this study, the effects of limited hydrolysis and/or high-pressure homogenization (HPH) treatment in acid conditions on the functional properties of oyster protein isolates (OPI) were studied. Protein solubility, surface hydrophobicity, particle size distribution, zeta potential, foaming, and emulsifying properties were evaluated. The results showed that acid treatment led to the dissociation and unfolding of OPI. Subsequent treatment such as limited proteolysis, HPH, and their combination remarkably improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
(51 reference statements)
3
9
2
Order By: Relevance
“…Reduction in particle size could be due to dissociation of larger protein molecules into smaller peptides molecule under enzymatic hydrolysis. Similar result was also observed in previous studies (Song et al., 2013; Yu et al., 2018) in which particle size of protein isolate was reduced after high‐pressure homogenization and limited hydrolysis treatment.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Reduction in particle size could be due to dissociation of larger protein molecules into smaller peptides molecule under enzymatic hydrolysis. Similar result was also observed in previous studies (Song et al., 2013; Yu et al., 2018) in which particle size of protein isolate was reduced after high‐pressure homogenization and limited hydrolysis treatment.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, increased absolute zeta potential after hydrolysis signified the stability of aqueous suspensions, which might be caused by the detachment of amino acid group, causing changes in protein charge (Adler‐Nissen, 1986). Similarly, in the previous study, zeta potential of chicken and oyster protein was significantly increased after hydrolysis (Chen et al., 2016; Yu et al., 2018).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The observation was in agreement with Chen et al [11]; the author found that the zeta potential of protein increased after HP treatment. In addition, the dissociation of an amino acid group could also result in an increase in protein charge [15].…”
Section: Resultsmentioning
confidence: 99%